2021
DOI: 10.1007/s00167-021-06594-9
|View full text |Cite
|
Sign up to set email alerts
|

High variability and lack of standardization in the evaluation of return to sport after ACL reconstruction: a systematic review

Abstract: PurposeReturn to sport (RTS) after ACL reconstruction (ACLR) has been recognized as an important outcome, which is associated with success of the surgery. This study aimed to assess the methods used to determine return to sport after ACLR in the published literature, report on variability of methods and evaluate their strength in establishing accurate RTS data. MethodsElectronic databases (PubMed, Cochrane Library and Embase) were searched via a defined search strategy with no limits, to identify relevant stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…ACL rupture is the most common knee ligament injury [ 36 ], and where individuals intend returning to sport, they are usually recommended for ACL reconstruction (ACLR) and rehabilitation [ 23 ]. After these, individuals are expected to be able to return to sport [ 33 ], but the time of return to sport varies between 6 months and 27 years [ 22 ]. Long-term negative effects include reduced physical activity and quality of life (QOL) [ 7 ], and increased risk of osteoarthritis [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACL rupture is the most common knee ligament injury [ 36 ], and where individuals intend returning to sport, they are usually recommended for ACL reconstruction (ACLR) and rehabilitation [ 23 ]. After these, individuals are expected to be able to return to sport [ 33 ], but the time of return to sport varies between 6 months and 27 years [ 22 ]. Long-term negative effects include reduced physical activity and quality of life (QOL) [ 7 ], and increased risk of osteoarthritis [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 10 , 29 Noted discrepancies across studies are often based on age, sex, specific sport, level of participation, and differences in surgical technique and postoperative rehabilitation. 6 , 21 , 24 , 28 30 Ardern et al 3 examined a cohort of 314 competitive athletes, demonstrating 93% RTS at both the competitive and the recreational levels. Lai et al 24 found that, in general, 83% of elite athletes (professional, National Collegiate Athletic Association Division I, or highest level of competition for their sport) were able to RTS after ACLR within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing DB vs. SB ACLR, some previous studies [ 16 ] demonstrated no significant differences in return to sport outcome between the two techniques. Some of these observed discrepancies in return to sport outcomes can be attributed to different patient populations (age, sex, specific sport, level of participation in sports and more) and different study methodologies [ 13 ]. In this work, return to sport is defined as return to running and return to pivoting sport, respectively.…”
Section: Discussionmentioning
confidence: 99%